Perbedaan Peran Ibu Primipara Dan Multipara Dalam Pengasuhan Bayi Baru Lahir - Koekoeh Hardjito; Sumy Dwi Antono; Erna Rahma Yani (coba, 2015)
Primipara mother is woman which has borned a baby aterm the first time. However multipara mother is woman which has been borned life a baby several times but it is not more than five times. Primiparous response as parents need more support from the environment and some women do not like to responsibilities at home and care for the baby. Whereas in multiparous would be more realistic in anticipating his physical limitations and can more easily adapt to the role of social interaction, in the sense of having a positive response as a parent. The role of both in interaction and mothering of newborn baby were observationed either from feeding, interest, respons, speech and touch by FIRST observation method. Many things influencing interaction and ability of mother and mothering baby, one of them are experience of mother bears and takes care of child before it. This research aim to see is there are many difference the role of primipara and multipara mother in mothering of newborn baby that analized with FIRST observation method. Research design used study comparative with design sistematic of random sampling technic for gathering of the sample. Obsevation has been to 53 mother of post partum that consisted of 25 primipara and 28 multipara in Aura Syifa Hospital at Kediri. These observation has been done once between first day up to seventh day after delivering birth. Testing of data was done by Man-Whitney U Test with p value= 0,036 (α= 0,05). The result of research showed there are difference significantly between the role of mother primipara and multipara in mothering of newborn baby. Interaction between mothers with baby and mothering pattern of newborn baby are multipara mother better than primipara mother with FIRST observation method. Key word: the role, primipara, multipara, mothering